2017
DOI: 10.1186/s12964-017-0179-9
|View full text |Cite
|
Sign up to set email alerts
|

LASP2 suppresses colorectal cancer progression through JNK/p38 MAPK pathway meditated epithelial-mesenchymal transition

Abstract: BackgroundLASP2 (LIM and SH3 Protein 2) is a small focal adhesion protein belongs to nebulin protein family. As the newest member of nebulette family, the function of LASP2 remains to be identified.MethodsThe relationship between LASP2 expression and clinical characteristics of CRC was analyzed in 89 paraffin-embedded archived CRC specimens by immunohistochemistry (IHC). The effects of LASP2 on cell growth and migration were examined in vitro, using CCK-8 and transwell assays. Western blotting was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…There is an association between LRH1 and β‐catenin, which subsequently induces intestinal cell proliferation and tumorigenesis in colon cancer . Indeed, when cancer cells activate EMT progression and obtain stem‐cell‐like potential, the likelihood of metastasis is indicated . In breast cancer, LRH1 is involved in EMT progression, and LRH1 overexpression promotes cell motility and invasion by regulating E‐cadherin and MMP9 .…”
Section: Discussionmentioning
confidence: 99%
“…There is an association between LRH1 and β‐catenin, which subsequently induces intestinal cell proliferation and tumorigenesis in colon cancer . Indeed, when cancer cells activate EMT progression and obtain stem‐cell‐like potential, the likelihood of metastasis is indicated . In breast cancer, LRH1 is involved in EMT progression, and LRH1 overexpression promotes cell motility and invasion by regulating E‐cadherin and MMP9 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although LASP2 and LASP1 share high similarity in the structure, B Wang et al (2017). detected an opposite distribution and function of LASP1 and LASP2 in CRC cells.…”
mentioning
confidence: 93%
“…It has been reported that the JNK pathway activation promotes the proliferation of cancer cells by reducing the expression level of cell cycle inhibitors p16 or p21 . What's more, the JNK pathway could accelerate cancer cells migration through inducing the EMT which is accompanied with the changed expression of related proteins such as ZO‐1 and Vimentin . EMT‐like processes have been implicated in hematological malignancies in addition to solid tumors, while p38/JNK pathway was shown to be involved in portulacerebroside A‐mediated suppression of adhesion, migration and invasion in AML cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…27,28 What's more, the JNK pathway could accelerate cancer cells migration through inducing the EMT which is accompanied with the changed expression of related proteins such as ZO-1 and Vimentin. 29 EMT-like processes have been implicated in hematological malignancies F I G U R E 6 PRDM5 overexpression accelerates the growth of OCI-AML leukemic xenograft tumors. A, Representative nude mice image showed the CT tumor on the left flank and the PRDM5 OE tumor on the right flank.…”
Section: Discussionmentioning
confidence: 99%